Eco-Pesantren: The Foundation for Building a Sustainable Environmental Mosaic - Abdullah Mufid Mubarrok; Mohammad Sholeh (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The implementation of an environmentally friendly education system is increasingly gaining attention in sustainable social development. This approach includes efforts to encourage the development of environmentally conscious Islamic boarding schools (pesantren). In their development, Islamic boarding schools are not only known as religious educational institutions and social centers, but awareness of the surrounding environment is still often neglected. Using qualitative methods and a library research approach, this article aims to examine community service activities that lead to a paradigm shift in Islamic boarding schools. The results of the study indicate that Islamic boarding schools not only carry out educational functions but also play a vital role as agents of social transformation to improve the quality of life of the surrounding community. Furthermore, Islamic boarding schools can be pioneers in creating a sustainable environment. This research uses a literature review method to develop an Eco-Pesantren strategy and evaluate its impact on socio-economic aspects, both for the Islamic boarding schools themselves and the wider community. The Eco-Pesantren concept is positioned as a foundation for teaching that prioritizes the value of environmental concern, while environmental theology enriches this concept with a profound philosophical-ecological approach.